Counseling for Bipolar Disorder in an Attempt to Raise Awareness in the EastJava Region using the Zoom Platform - Iwan Sis Indrawanto; Muhamad Nurul Robby Robby; Hanna Cakrawati; Salma Ardhya Maharani; Muhammad Adin Nugroho; Salwa Rizqi Salsabila; Anggieta Asdi Estiningtyas (Universitas Muhammadiyah Malang, 2025)
Referring to the bipolar prevalence rate in East Java which is relatively high, public awareness in countries with a dominant percentage of lower middle income is still relatively low due to the many clashes and interactions in daily life with many conflicts, culture, trauma, perspectives, level of education, limitations to health services’ access, and disparities in social status, as well as the minimal allocation of government policy focus related to mental health aspects. The low level of knowledge and awareness as well as the direction of intervention towards mental health will have an impact on the stability and resilience of individuals and groups in maintaining their quality of life due to ignorance regarding defensive mechanisms and seeking appropriate health service assistance, which then becomes a repeating cycle and becomes a problem that is difficult to resolve. Purpose: The aim of this program is to raise awareness of bipolar disorder among the people in the East Java region. Methods: The community service activity carried out in this study was counseling about Bipolar. Education includes definitions, causes, risk factors, environmental manipulation therapy, and prevention of Bipolar disorder. Pretest and posttest were also carried out to measure public knowledge about Bipolar disease using a Google form-based questionnaire. Counseling is carried out online using the Zoom meeting platform. Results: There were 23 respondents who completed the questionnaire out of the 39 counseling participants. 34.78% to 100% of respondents were distributed according to their level of knowledge prior to pre-counseling and following counseling. Conclusion: After receiving counseling, everyone of the 23 study participants had a solid understanding of bipolar illness.